Vítězslav Gardavský (1923-1978) - Military Reformer, Philosopher and Writer - Polnar, Stanislav (Historica Olomucensia, 2022)
The personage of Colonel doc. PhDr. Vítězslav Gardavský, CSc. (1923-1978) is perceived primarily in the context of his writing and philosophical output. His activities in army and military science are, however, often neglected. Gardavský greatly impacted the Marxist-Christian dialogue of the 1960s, when his career as a military teacher and scholar culminated. His views on the position of Germany and the German nation in European society and politics also greatly impacted the new views of Czechoslovak strategies and doctrines. Reformed military science on the defence of Czechoslovakia was summarised in the so-called 68 Memorandum, which came about in the spring of 1968. Gardavský not only signed this, but also agreed with its ideological concept. The personage of Gardavský is a clear example of the situation when a scholar, despite his completely civilian focus, can markedly formulate in specialised scholarship even somewhat remote questions of military science and the defence of the state.
Keywords: Prague Spring; Military reform; Military science; Military education; Marxist philosophy; Memorandum 68